How Do I Reverse Oral and Parenteral Anticoagulants? - Koscielny, Jürgen; Rutkauskaite, Edita; Sucker, Christoph; von Heymann, Christian (Hämostaseologie, 2020)
An understanding of reversal strategies alone is important to safely and effectively care for patients in cases of bleeding or invasive procedures. The recent diversification in the number of licensed anticoagulants makes an understanding of drug-specific reversal strategies essential. Intravenous or oral vitamin K can reverse the effect of vitamin K antagonists (VKAs) within 12 to 48 hours and is indicated for any bleeding or an international normalized ratio >10 or 4.5 to 10 in patients with additional risk factors for bleeding. Furthermore, an additional administration of prothrombin complex concentrate (PCC) may be necessary in cases of major bleeding related to VKA. Protamine (chloride or sulfate) fully reverses the effect of unfractionated heparin and partially in low-molecular-weight heparin. Idarucizumab has been approved for dabigatran reversal, whereas andexanet alfa is approved for the reversal of some oral factor Xa inhibitors (apixaban, rivaroxaban). PCC seems to enhance the haemostatic potential for the reversal of the effect of FXa-inhibitors. So far, there are promising but only limited data on the efficacy of this approach available. Each reversal strategy needs an adequate management beyond the hemostatic treatment (volume replacement, stabilization of homeostasis, e.g., pH and temperature, resumption of anticoagulation after successful treatment of bleeding, etc.) that is crucial for the successful management of acute bleedings, urgent high-risk surgery, thrombolytic therapies or thrombectomies as well as overdosing of anticoagulants.
Keywords: oral and parenteral anticoagulants; reversal strategy; vitamin K antagonist